(tanx+1/tanx)cos^2 x等于
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 16:42:43
(tanx+1/tanx)cos^2x等于(tanx+1/tanx)cos^2x等于(tanx+1/tanx)cos^2x等于(tanx+1/tanx)cos^2x=(sinx/cosx+cosx/s
(tanx+1/tanx)cos^2 x等于
(tanx+1/tanx)cos^2 x等于
(tanx+1/tanx)cos^2 x等于
(tanx+1/tanx)cos^2 x
=(sinx/cosx+cosx/sinx)cos^2x
=sinx cosx+cos^3x/ sinx
=cosx(sinx +cos^2x/sinx)
=ctgx(sin^2x+cos^2x)
=ctgx
(tanx+1/tanx)cos^2 x等于
(tanx+1/tanx)cos^2 x等于
[tanx+(1/tanx)]cos^x
﹙tanx+1/tanx)cos^2x等于
提问数学难题求证:sin^2x*tanx+cos^2x/tanx+2sinx*cosx=tanx+1/tanx
tanx/(cos^2)x dx
y=(tanx-1)cos^2x最大值y=(tanx-1)cos²x最大值
证明1-2sinxcosx/cos^2x-sin^2x=1-tanx/1+tanx
证明:(1+2sinXcosX)/(sin^2X-cos^2X)=(tanX+1)/(tanX-1)
求证1+2sinxcosx/cos^2x-sin^2x=1+tanx/1-tanx
求证(1-2sinxcosx)/(cos^2x-sin^2x)=(1-tanx)/(1+tanx)SOS!
(cos^2x-sin^2x)/(1-2sinxcosx)=(1+tanx)/(1-tanx)证明题
求证:(1-2sinxcosx)/(cos^2x-sin^2x)=(1-tanx)/(1+tanx)
1-2sinx cosx /COS^2X-SIN^2X =1-tanx/1+tanx 求证
若tanx/tanx-1=-1 求sin(π/2+x)cos(3π/2-x)
求证(1-2sinxcosx)/(cos²x-sin²x)=(1-tanx)/(1+tanx)
化简sin^x*tanx+cos^x*1/tanx+2sinx*cosx
求证:1/tanx-tanx=(2cos^2x-1)/sinx*cosx